PERLINDUNGAN HUKUM BAGI KONSUMEN ATAS BEREDARNYA PRODUK PANGAN YANG TIDAK MEMILIKI IZIN EDAR DARI BADAN PENGAWAS OBAT DAN MAKANAN - Arini Rizkia, (2022)
The distribution permit issued by BPOM for food products is a form of approval for food products to be circulated to the public that are guaranteed safe for consumption.. However, nowadays there are many business actors who are not responsible for the food products being sold that do not have a distribution permit because they do not meet the requirements for a distribution permit, making this action a violation of the existing laws and regulations regarding distribution permits for food products. This study uses a normative juridical legal research method with a law approach and a case approach with secondary data sources obtained from literature studies which are then analyzed qualitatively in processing the data. So that after analyzing it, the actions taken by business actors result in the violation of consumer rights where there must be legal protection for consumers and regulations regarding distribution permits. Where business actors are required to be responsible for the actions taken, namely by paying for losses that have an impact on consumers in accordance with Article 19 of Law Number 8 of 1999 concerning consumer protection. It is hoped that business actors will pay more attention to existing regulations regarding distribution permits so that no more consumers are harmed because their rights are violated, for consumers to be wiser and more alert in every purchase of food products, and for the Government and BPOM to reinforce existing rules by imposing sanctions. which discourages business actors.